Analisis Dampak Kecanduan Aplikasi Mobile Legend Dikalangan Mahasiswa Pendidikan Bahasa Sastra Semester 6 - Sefenrius Buulolo; Sarhad Niat Putri Harefa; Krisnawati batee; Noveri Amal Jaya Harefa (Departement of Mathematics Education, 2024)
The purpose of the study was to describe the impact of addiction to the Mobile Legend application among Semester Vi Literature Language Education students The method used in this research is a qualitative method. The data collection stage is that data can be used in various ways. The data collected is in the form of collecting primary data. For the main literature study in the data collection method is to use the documentation method. After collecting data, the next step is the data analysis stage, namely inductive qualitative data analysis, data presentation, and conclusions. Then the data is reviewed descriptively and the presentation of the results of data analysis is presented in the form of interview results by explaining the impact of addiction to the Mobile Legend application among 6th semester literature language education students. Aspects of Motivational Value Namely Game Addicts What is Motivated Namely Filling Free Time and Entertainment, Interesting Features and Social Environments that Encourage Playing, Building Relationships and Social Interaction with Friends; (2) Advantages with Yourself Namely Recognition in the Game and Potential Income from Content, Making New Friends and Opportunities to Participate in Tournaments, Training Communication in Teams and Entertainment; (3) Negative Impacts Difficulty Managing Time, Irregular Eating and Sleeping Patterns, and Increased Emotions, Wasting Time, Health Problems, and Decreased Academic Achievement, Health Problems, Lack of Sleep, and Spending Money. As a result, playing Mobile Legends provides some positive impacts such as entertainment, skill enhancement, and income opportunities.